ORGANO-SOLUBLE AROMATIC POLYAMIDE FILMS - LEE, CJ; PARK, S; KIM, SY; LEE, YJ; MIN, BG; SON, TW; KIM, BC (WILEY-BLACKWELL, 1995)
To make stable isotropic aramid solutions and films, 6-amino-2-(4-aminophenyl)-4-phenyl quinoline (QDA) was used as base diamine, and copolymerized using terephthaloyl chloride (TPC) with p-phenylene diamine(PPD), 2,2'-bis(trifluoromethyl)benzidine (PFMB), and oxydianiline (ODA) as second diamine, respectively. Homogeneous viscous polymerization solutions based on QDA were obtained, and films prepared from them were transparent and amorphous. The reactivity of QDA with TPC was almost equal to that of PPD; the reactivity of PFMB was low due to the electron withdrawing groups (-CF3) attached to the ortho positions of the benzene rings. Bulkiness and flexibility of the monomer structure widened the range of stable conditions in polymer solution. A rod-like structure of the monomer caused drawability to decrease. QDA/ODA copolymer films could be drawn well, probably as a result of the flexible linkage of ODA, and had high tensile strength (86 kg/mm(2)). High modulus, 3.1 x 10(3) kg/mm(2), was obtained in QDA/PPD copolymer films. Tensile strength and modulus increased withdraw ratio. T-g and T-m were not seen by DSC and T-d of the polymers was as high as c. 500 degrees C. Excess drawing caused the films to be fibrillated, affecting their tensile properties.